Characterization of the complete chloroplast genome of Carya laciniosa (F.Michx.) G.Don (Juglandaceae) - Min Zhai; Xiao-Dong Jia; Ji-Yu Zhang; Zhong-Ren Guo; Ji-Ping Xuan (Mitochondrial DNA. Part B. Resources, 2021)
Carya laciniosa (F.Michx.) G.Don is a slow-growing valuable tree in the family Juglandaceae. In this research, we first reported the chloroplast genome sequence of C. laciniosa. The chloroplast genome was a circular form with 160,832 bp in size, comprising four subregions: a large single-copy (LSC) region of 90,065 bp, a small single-copy (SSC) region of 18,791 bp, and two copies of inverted repeats (IRs; IRa and IRb) of 25,988 bp each. A total of 132 genes were annotated in the chloroplast genome of C. laciniosa, including 87 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The overall GC content of the whole genome was 36.14%. Phylogenetic analysis suggested that C. laciniosa was closely related to C. ovata.